The emergence of subjects in Lebanese two-year-olds - ABBOUD, Layal; CHOUEIRI, Lina; SEIFEDDINE, Nour; TULLER, Laurice (Journal of child language, 2024)
In Lebanese Arabic, lexical subjects may occur before or after verbs, but only before non-verbal predicates. Analysis of spontaneous language samples from 19 two-year-old children shows that postverbal (VS) and preverbal (SV) subjects emerge simultaneously. The youngest children displayed no VS-SV difference in frequency. A slight preference for SV is observed in older children. No preference for SV subjects was found in the speech of the mothers of the younger or older children. Lexical subjects systematically appeared before non-verbal predicates. We interpret these results as evidence for early knowledge of syntactic movement, consistent with Wexler’s (1998) Very Early Parameter Setting.